2020
DOI: 10.1111/febs.15520
|View full text |Cite
|
Sign up to set email alerts
|

Linking hyperosmotic stress and apoptotic sensitivity

Abstract: Cellular responses to hypertonic stress and how these are linked to the induction of or sensitisation to cell death signals are incompletely understood and rarely studied in cancer. Using cell lines derived from head and neck squamous cell carcinoma (HNSCC), Heimer et al. demonstrate that hypertonic environments neutralise the antiapoptotic Bcl-2 family member Mcl-1 by upregulating its antagonist Noxa. Consequently, hypertonically stressed HNSCC cells rely solely on Bcl-xL for survival and succumb to apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Interestingly, DPSC lysate was able to effectively reduce the viability of lung cancer cells and induce apoptosis in a concentration-dependent manner. Western blot results showed that the expression levels of pro-apoptotic proteins in the 1:1 group of DPSC lysate were much higher than those in the other two lysate groups, probably because the high concentration of 1:1 DPSC lysate caused changes in the osmolarity of the cancer cell environment, leading to apoptosis [ 40 ]. Apoptosis is a programmed death and is an important self-stabilizing mechanism in organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, DPSC lysate was able to effectively reduce the viability of lung cancer cells and induce apoptosis in a concentration-dependent manner. Western blot results showed that the expression levels of pro-apoptotic proteins in the 1:1 group of DPSC lysate were much higher than those in the other two lysate groups, probably because the high concentration of 1:1 DPSC lysate caused changes in the osmolarity of the cancer cell environment, leading to apoptosis [ 40 ]. Apoptosis is a programmed death and is an important self-stabilizing mechanism in organisms.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the liver cancer cell line HepG2 as the model cell type given that the cell line recapitulates characteristics of hepatoblasts as well as epithelial-like HCC 41 . Several previous studies showed that acute osmotic stress induces cell death 42,43 . Here we found HepG2 cells at all different compression levels after long-term treatment (5 days) not only survived better than under control conditions but also underwent a drastic morphological change (Fig.…”
Section: Hyperosmolarity-induced Volumetric Compression Drives Morpho...mentioning
confidence: 99%